Perancangan Zionis Ke Arah Pembentukan Negara Israel - Mohd Nor, Mohd Roslan; Zakaria, Nor Dalila (Jurnal Usuluddin, 2009)
The official establishment of the State of Israel in 1948 on the land of Palestine was a result of hardworking and strategic planning of Zionists. By using several methods and their continuous effort including the moral boost that they received from the west which always supported Zionists effort, has given a huge advantage to the Zionists. This article will attempt to explore the Zionists plan which they have succeeded in taking over Palestine and established the state that is merely for the Jews